Comparison of intravitreal bevacizumab treatment between phakic and pseudophakic neovascular age-related macular degeneration - Ozkaya, Abdullah; Alkin, Zeynep; Perente, Irfan; Yuksel, Kemal; Baz, Okkes; Alagoz, Cengiz; Yazici, Ahmet Taylan; Demirok, Ahmet (Nepalese Journal of Ophthalmology, 2014)
Introduction: Before the era of intravitreal anti-vascular endothelial growth factor (anti-VEGF) treatment, only prevention for visual loss might have been achieved in a limited number of neovascular age-related macular generation (nAMD) patients with different treatment options. Objective: To compare the efficacy of intravitreal bevacizumab (IVB) for the treatment of nAMD between phakic and pseudophakic eyes. Materials and methods: The newly diagnosed nAMD patients were included in this retrospective study. The patients were divided into the phakic and pseudophakic groups. Initially, the patients received three consecutive, monthly, IVB injections, and then the treatment was continued on an as-needed regimen. The patients were examined monthly, and the data at the baseline, at 3, 6, 9, and 12 months and at the last follow-up were evaluated. The changes in the visual acuity (VA), central retinal thickness (CRT) and the number of injections were compared between the two groups. Results: The study included 62 eyes of 62 patients (39 phakic, and 23 pseudophakic patients). The mean follow-up time was 19.7 and 17.2 months in the phakic and pseudophakic groups, respectively (p = 0.06). The mean Log MAR VA at the baseline, 12 months and the last follow-up was 0.82, 0.72 and 0.75 in the phakic group and 0.77, 0.67, and 0.68 in the pseudophakic group, respectively. The change in the mean BCVA from the baseline to 12 months and at the last follow-up was not statistically different between the two groups (p = 0.9 and p = 0.7, respectively). The mean injection number at 12 months was 4.5 and 4.9 in the phakic and pseudophakic group, respectively (p = 0.2). Conclusion: The beneficial effect of IVB is equal in both the phakic and pseudophakic group of nAMD patients. The functional and anatomical outcomes of the treatment and the number of injections were similar in the two groups. DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11706 Nepal J Ophthalmol 2014; 6(12): 145-152